Urban climate research in Gdańsk and Gdynia - Filipiak, Janusz; Miętus, Mirosław (Acta Geographica Lodziensia, 2019)
A short history and the results of urban climate research in Gdańsk and Gdynia are presented in the paper. The initial research of Gdańsk’s climate was associated with the early beginning of meteorological measurements in 1739. In the last decades of the 19th century, the importance of studies devoted to ensuring the safety of shipping and harbour activity increased significantly. The interwar period was characterized by great development of meteorological observatories in Gdańsk and Gdynia. The research efforts were particularly dedicated to the recognition of local climatic conditions, including the phenom-enon of sea breeze. In the post-war period, advanced field research was undertaken to characterize the characteristic features of spatial variability of meteorological elements in Gdynia and Gdańsk. Various aspects of applied urban climatology are present in the research of the last decades of the 20th century and present times.